Settling the Fisheries: Pre-Confederation Crown Policy in Upper Canada and the Supreme Court's decisions in R. v. NIKAL and LEWIS - Blair, Peggy (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 2001)
Although a casual reading of the Supreme Court of Canada's decisions in R. v. Nikal and R. v. Lewis might suggest otherwise, this article will argue that Court's decisions in two recent British Columbia aboriginal fishing cases do not apply in Ontario. In doing so, it will be shown that the Supreme Court of Canada relied on evidence of historic Crown policies towards aboriginal fishing rights in Upper Canada in the absence of appropriate context as to when, how and why those policies evolved. As a result, the Court wrongly concluded that fisheries could not be the subject of exclusive aboriginal rights.